Calmodulin-like skin protein is downregulated in human cerebrospinal fluids of Alzheimer's disease patients with apolipoprotein E4; a pilot study using postmortem samples. (2nd September 2017) - Hashimoto, Yuichi; Umahara, Takahiko; Hanyu, Haruo; Iwamoto, Toshihiko; Matsuoka, Masaaki
Abstract: Objective: Calmodulin-like skin protein (CLSP) is a secreted peptide that inhibits neuronal cell death, linked to Alzheimer's disease (AD), by binding to the heterotrimeric humanin receptor and activating an intracellular survival pathway. CLSP is only expressed in skin keratinocytes and related epithelial cells, circulates in the blood stream, and passes the blood–cerebrospinal fluid (CSF) barrier. In the current study, we addressed the issues as to whether CLSP functions in the central nervous system and whether the concentration of CLSP is reduced in the CSFs of AD patients. Methods: Mice were intraperitoneally injected with 5 nmol of recombinant human CLSP. At 1h after the injection, the mice were sacrificed for the analysis of the existence of human CLSP in blood and interstitial fluid (ISF)-containing brain samples. Using postmortem CSF samples, we next determined the concentrations of CLSP in CSFs of human AD and control cases. Results: Intraperitoneally administered recombinant human CLSP circulated in the blood stream and reached the brain interstitial fluid. The concentrations of CLSP in CSFs of human AD and control cases are sufficient to exhibit the CLSP activity. Although the concentrations of CLSP in CSFs were not significantly different between AD and control cases, the concentrations of CLSP are lower in the AD cases with the apolipoprotein E4 genotype than in the AD cases without the apolipoprotein E4 genotype. Discussion: The first result indicates that CLSP enters the central nervous system through the blood–brain barrier. The second result suggests that CLSP functions in the human brains. The third result may exclude the possibility that the downregulation of the CLSP level is involved in the AD pathogenesis. The last result may contribute to the better understanding of the AD pathogenesis from the standpoint of the apolipoprotein E genotype.